A pinnacle of feeling : American literature and presidential government - McCann, Sean, 1962- (20/21 (Princeton, N.J.), 2008)
There is no more powerful symbol in American political life than the presidency, and the image of presidential power has had no less profound an impact on American fiction. A Pinnacle of Feeling is the first book to examine twentieth-century literature's deep fascination with the modern presidency and with the ideas about the relationship between state power and democracy that underwrote the rise of presidential authority. Sean McCann challenges prevailing critical interpretations through revelatory new readings of major writers, including Richard Wright, Gertrude Stein, Henry Roth, Zora Neale.